Nanomaterials in the Wound Healing Process: New Insights and Advancements - Tanikan Sangnim; Vivek Puri; Divya Dheer; D. Nagasamy Venkatesh; Kampanart Huanbutta; Ameya Sharma (MDPI AG, 2024)
Wounds, which are becoming more common as a result of traumas, surgery, burns, and chronic illnesses like diabetes, remain a critical medical problem. Infectious bacteria impact the healing process, particularly if its biofilm (biological films) leads to a prolonged effect. Nanomaterials have emerged as promising candidates in the field of wound healing due to their unique properties and versatile applications. New insights into the interactions between nanomaterials and wound microenvironments have shed light on the mechanisms underlying their therapeutic effects. However, a significantly minimal amount of research has been carried out to see if these nanomaterials significantly promote the wound healing process. In this review, we provided an outline of the various types of nanomaterials that have been studied for healing wounds and infection prevention. Overall, the utilization of nanomaterials in wound healing holds great promise and continues to evolve, providing new opportunities for the development of effective and efficient wound care therapies.